Levels of inorganic arsenic in regularly milledlocal rice (Oryza Sativa L.) in identified wet markets in National Capital Region, Philippines - Darroca, Kezia B.
This study determined the levels of inorganic arsenic in regularly milled local rice obtained from three identified wet markets in National Capital Region, Philippines. Consultation with the Department of Agriculture – National Food Authority showed that rice available in the Philippine markets were either locally sourced or exported. Survey among identified rice retailers in Balintawak (n=3), Commonwealth (n=3), and Alabang (n=1) Markets determined that the retailed regularly milled local rice in these markets were commonly from Pangasinan, Bulacan, Nueva Ecija, Isabela, Ifugao, Mindoro, and Tarlac. The inorganic arsenic levels of the regularly milled local rice samples from Balintawak (n = 7 ), Commonwealth (n = 8), and Alabang (n = 7) Markets were analyzed using AOAC SMPR 2015.006. The levels ranged from 0.019  0.0001 to 0.055  0.0007 mg/kg which did not exceed the 0.20 mg/kg maximum residue level of inorganic arsenic set by CODEX STAN 193-1995 rev 2014 for rice. Inorganic arsenic levels of rice in various countries exporting rice to the Philippines such as Thailand, India, China, and Pakistan were retrieved from literatures. Compared with this guideline value, the estimated dietary exposure of the Filipino consuming population to inorganic arsenic in local and imported rice range from 1.83% to 4.34% of the PTWI. These hazard levels were used to estimate the dietary exposure of the general Filipino consuming population (body weight = 55kg ) which ranged from 0.0002 mg/kgbw to 0.002141 mg/kgbw using the mean daily rice intake of Filipino households and ranged from 0.0007 mg/kgbw to 0.0051 mg/kgbw if the 97.5th percentile rice intake was considered. Generally, these values are below Provisional Tolerable Weekly Intake (PTWI) set by the Joint WHO/FAO Expert Committee on Food Additives (JECFA) on its 33rd meeting in 2011 at 0.015 mg/kg bw (TRS 776-JECFA 33/27).